The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.2174/187152706777950693
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Profile of Antipsychotics at Monoamine Receptors: Atypicality Beyond 5-HT2A Receptor Blockade

Abstract: Antipsychotic drugs (APD) are widely prescribed for the treatment of schizophrenia. The APD are differentiated into typical and atypical based on the lower incidence of extra-pyramidal side-effects associated with the newer atypical APD. It was suggested that atypicality may arise from an interaction with the 5-hydroxytryptamine (5-HT)(2) receptor and specifically on the 5-HT(2):dopamine D(2) affinity ratio. It is now realised that multiple subtypes of these receptors exist and that in addition, atypical APD i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Thus, our analysis suggests that the therapeutic effects of atypical antipsychotic medications are determined by interactions among three different domains: (1) We are not aware of other studies demonstrating that serotonin 5-HT 2C receptor blockade has opposite effects in typical and atypical antipsychotic medications. It has previously been suggested, however, that both 5-HT 2C antagonism (Meltzer et al, 2003;Meltzer, 1995;Wood et al, 2006) and 5-HT 2C receptor stimulation (Meltzer, 1999;Marquis et al, 2007) could facilitate antipsychotic activity. Our data support the view that this seemingly paradoxical finding may result from the relatively higher 5-HT 2A receptor blockade in atypical vs typical medications.…”
Section: Atypical Antipsychotic Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our analysis suggests that the therapeutic effects of atypical antipsychotic medications are determined by interactions among three different domains: (1) We are not aware of other studies demonstrating that serotonin 5-HT 2C receptor blockade has opposite effects in typical and atypical antipsychotic medications. It has previously been suggested, however, that both 5-HT 2C antagonism (Meltzer et al, 2003;Meltzer, 1995;Wood et al, 2006) and 5-HT 2C receptor stimulation (Meltzer, 1999;Marquis et al, 2007) could facilitate antipsychotic activity. Our data support the view that this seemingly paradoxical finding may result from the relatively higher 5-HT 2A receptor blockade in atypical vs typical medications.…”
Section: Atypical Antipsychotic Medicationsmentioning
confidence: 99%
“…In contrast, the correlation between serotonin 5-HT 2C receptor affinity and clinically effective antipsychotic drug dose for atypical antipsychotic medications differs from the correlation for typical medications (p ¼ 0.02), is in the opposite direction, and the degree of correlation is less pronounced (Figure 3). Although a potential role for 5-HT 2C receptor antagonism in the therapeutic effect of atypical antipsychotic medications has previously been discussed (Meltzer et al, 2003;Meltzer, 1995;Wood et al, 2006), it has also been suggested that 5-HT 2C agonism could be therapeutic (Meltzer, 1999;Marquis et al, 2007) based on a wide range of preclinical measures demonstrating that serotonin 5-HT 2C receptor stimulation inhibits the mesolimbic DA system (Alex et al, 2005;Pozzi et al, 2002;De Deurwaerdere and Spampinato, 1999;Millan et al, 1998;Di Matteo et al, 2002). These findings are consistent with our observation, and suggest a potential mechanism for 5-HT 2C receptor blockade to worsen psychotic symptoms.…”
Section: Typical Antipsychotic Medicationsmentioning
confidence: 99%
“…While conventional D 2 receptor-blocking antipsychotics primarily have clinical effect on positive symptoms of schizophrenia, the second-generation antipsychotics, which have a broader receptor profile, seem to have some beneficial effects on negative symptoms and moderate effects on cognitive deficits as well (Meltzer and McGurk 1999;O'Grada and Dinan 2007;Pratt et al 2008;Remington and Kapur 2000). The additional 5-HT 2A receptor antagonistic property of some second-generation antipsychotics is assumed to be involved in their therapeutic mechanism of action (Wood et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, sertindole has high 5-HT6 receptor affinity ( in vitro binding affinity = 9.13 p K i value, − log M ) 20. Combined dopamine D 2 and serotonin 5-HT 2A receptor antagonism is a feature common to most atypical antipsychotics and is thought to contribute to their therapeutic effect on schizophrenic symptoms 2123. Results from a positron emission tomography (PET) study on healthy subjects showed that sertindole up to 12 mg/day induced a 5-HT 2A receptor occupancy of approximately 100%, thus confirming preclinical data on sertindole receptor affinity 24.…”
Section: Pharmacological Profilementioning
confidence: 99%